The Rebound Effect and the Proposed Rollback of U.S. Fuel Economy Standards. (9th January 2020) - Gillingham, Kenneth T
Abstract: The Trump administration's August 2018 proposed rollback of the 2020–2026 fuel economy standards has been the subject of great controversy in the policy community. The justification for the rollback was based on an analysis indicating that the previous fuel economy standards would be associated with more than 12, 000 additional fatalities over the lifetime of the vehicles affected by the standards. The largest contributor to these estimated fatalities is the rebound effect assumed in the analysis, which was increased from 10 percent in the previous rule to 20 percent in the proposed rule. This article summarizes the current state of knowledge about the rebound effect as it relates specifically to fuel economy standards. A careful review of the recent literature supports a central estimate closer to 10 percent, thus undermining a key argument that has been used to support the rollback of the standards. However, there are wide bounds of uncertainty around this central estimate as well as several poorly understood factors not accounted for in the central estimates, which further increase our uncertainty about the rebound effect. This highlights the importance of sensitivity analysis and further research on this policy-relevant topic.